Informal institutions, shareholder coalitions, and principal-principal conflicts - Sauerwald, S.; Peng, Mike (Springer New York LLC, 2013)
How do informal institutions affect conflicts between controlling and minority shareholders, also known as principal-principal (PP) conflicts? The dominant formal institution-based view of corporate governance suggests that legal rules and regulations are crucial for the protection of shareholder rights. While this perspective has significantly advances our understanding of international corporate governance, we suggest that more attention to informal institutions may complement the formal approach. First, we utilize social identity theory to shed light on the formation of shareholder coalitions. Second, we draw on research involving informal institutions such as culture and trust to better understand PP conflicts. Overall, we extend the growing literature on PP conflicts by an explicit focus on informal institutions.